TAENIA SPP.: FORMS OF DETECTION BY LABORATORY TESTS (CIPEEX, 2024)
The aim of this study was to highlight the diagnosis of Taenia solium and T. saginata. Cattle and pigs are intermediate hosts of tapeworms, the etiological agents of taeniasis, an intestinal parasitosis of humans, whose hermaphroditic adult worm is in the small intestine. It is known as solitary and contact with the parasite is given through the ingestion of raw or undercooked meat, which if contaminated will present the cysticerco larva. The cisticerco larva in raw meat is known as canjiquinha. The adult worm of T. saginata can reach 12 meters, and that of T. solium can be eight meters. They produce about a thousand proglottids in their half-life that generate about 50 thousand eggs. However, tapeworm infection usually progresses with mild symptoms, although there may be abdominal pain, nausea, weakness, weight loss, increased appetite, diarrhea, and constipation. Laboratory diagnosis can be performed by visualizing eggs and proglottids in the feces. However, the differential diagnosis between the two species, Taenia solium and Taenia saginata, can be complicated at the level of microscopic visualization of the eggs, since both species produce spherical eggs with a thick double shell, brownish and with radial streaks, with an interior filled with the oncosphere or hexacanth embryo, which has three pairs of aculeus or hooks. For the visualization of the proglottids, the general or float method can be used. As for proglottids, they are difficult to visualize in the feces, and clarification with acetic acid can be performed. Antibody and DNA tests are not widely used, although they are available. ELISA coproantigen testing, although rare outside of research laboratories, significantly increases sensitivity and is useful for confirming treatment, particularly in endemic areas.
Keywords: intestine; tapeworm; ox; pig